BACH1 promotes clear cell renal cell carcinoma progression by upregulating oxidative stress‐related tumorigenicity. Issue 2 (1st November 2022) - Takemoto, Kenshiro; Kobatake, Kohei; Miura, Kento; Fukushima, Takafumi; Babasaki, Takashi; Miyamoto, Shunsuke; Sekino, Yohei; Kitano, Hiroyuki; Goto, Keisuke; Ikeda, Kenichiro; Hieda, Keisuke; Hayashi, Tetsutaro; et al.
Abstract: The carcinogenesis and progression of renal cell carcinoma (RCC), a heterogeneous cancer derived from renal tubular epithelial cells, is closely related to oxidative stress responses (OSRs). Oxidative stress responses participate in various biological processes related to the metabolism and metastatic potential of cancer such as inflammation, epithelial–mesenchymal transition (EMT), and angiogenesis. In this study, we investigated the role of broad complex‐tramtrack‐bric‐a‐brac and cap 'n' collar homology 1 (BACH1), a key transcription factor for OSRs, in clear cell RCC (ccRCC) development and prognosis. The poor prognosis and elevation of serum inflammation markers in nephrectomized ccRCC patients were correlated with the intratumor expression of BACH1 accompanied by a downregulation of heme oxygenase‐1. BACH1 contributes to the invasion and migration abilities of RCC cell lines without affecting their proliferation in vitro. In contrast, BACH1 contributes to tumor progression in vivo, in relation to OSRs with the activation of EMT‐related pathways. BACH1 involvement in other OSR‐linked pathways, including inflammatory responses, angiogenesis, and mTOR signaling, was further revealed by RNA sequencing analysis of BACH1‐knockdown cells. In conclusion, the crucial role of BACH1 in the pathogenesis and poor prognosis of ccRCC through the promotion of OSRs is suggested. Abstract : The oxidative stress response factor BACH1 is deeply involved in the malignant progression of cancer. We elucidated the crucial contribution of BACH1 to renal cell carcinoma progression.